The ecology and conservation of the muriqui Brachyteles: reports from 2002-2005. Introduction - Strier, Karen B.; Pinto, Luiz Paulo S.; Paglia, Adriano; Boubli, Jean P.; Mendes, Sérgio L.; Marini-Filho, Onildo J.; Rylands, Anthony B. (Neotropical Primates, 2005)
No abstract